Natrium Benzoate Alleviates Neuronal Apoptosis via the DJ-1-Related Anti-oxidative Stress Pathway Involving Akt Phosphorylation in a Rat Model of Traumatic Spinal Cord Injury - Gao, Liansheng; Zhang, Zhongyuan; Xu, Weilin; Li, Tao; Ying, Guangyu; Qin, Bing; Li, Jianru; Zheng, Jingwei; Zhao, Tengfei; Yan, Feng; Zhu, Yongjian; Chen, Gao (Frontiers in Molecular Neuroscience, 2019)
This study aimed to explore the neuroprotective effects and mechanisms of natrium benzoate (NaB) and DJ-1 in attenuating reactive oxygen species (ROS)-induced neuronal apoptosis in traumatic spinal cord injury (t-SCI) rats. T-SCI was induced by clip compression. Western blotting was applied to assess the levels of DJ-1, oxidized DJ-1 (oxDJ-1), Akt, superoxide dismutase 2 (SOD2), p38 MAPK, Bax, Bcl-2, and cleaved caspase-3 (CC-3). DJ-1, CC-3, terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL), and NeuN double immunofluorescence staining was performed. ROS level, spinal cord water content (SCWC) and Evans blue (EB) extravasation was examined. Basso, Beattie, and Bresnahan (BBB) and inclined plane test (IPT) scores were evaluated. Ultrastructures of spinal cord neurons were observed. DJ-1 expressed in neurons and increased after t-SCI. At 24 h post-injury, the levels of p-Akt, SOD2, ROS, p-p38 MAPK/p38 MAPK ratio, and CC-3 increased, while the Bcl-2/Bax ratio decreased. NaB upregulated DJ-1, p-Akt, and SOD2, decreased ROS, p-p38 MAPK/p38 MAPK ratio, and CC-3, and increased the Bcl-2/Bax ratio, which were reversed by DJ-1 siRNA. The proportions of CC-3- and TUNEL-positive neurons also increased after t-SCI, which were reduced by NaB. These effects were reversed by MK2206. Moreover, the level of oxDJ-1 increased after t-SCI, which was decreased by DJ-1 siRNA, NaB or the combination of them. The proportion of mitochondrial vacuolization, SCWC and EB extravasation increased after t-SCI, which were ameliorated by NaB. NaB also improved the BBB and IPT scores, which decreased after t-SCI. In conclusion, NaB increased DJ-1, and thus reduced ROS and ROS-induced neuronal apoptosis by promoting Akt phosphorylation in t-SCI rats. NaB shows potential as a therapeutic agent for t-SCI, with DJ-1 as its main target.